God's rivals why has God allowed different religions? : insights from the Bible and the early church - McDermott, Gerald R. (Gerald Robert) (Downers Grove, Ill. : IVP Academic, 2007)
Using the teachings from the Old and New Testaments and reflections from a number of key theologians from the early church, the author suggests an answer to why God has allowed other religions.
The scandal of particularity : why has the true God come to only some people at some times? -- Not even in Israel have I found such faith : surprising knowledge of God among Bible people outside Israel and the church -- The Lord of Hosts : the Old Testament and the real existence of other gods -- Principalities and powers : the New Testament on other real supernatural powers besides God -- Seeds of the Word : Justin Martyr on seeds of the Word in other religions -- Divine pedagogy : Irenaeus explains how God uses the religions -- A divine gift to the Greeks : Clement of Alexandria and the Gentile covenants -- Diverse destinies by diverse choices : Origen's warnings about other religions -- What are the religions? and why are they there? : collecting the strands -- Appendix : God and the masculine pronoun.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Christianity and other religions; Religious pluralism -- Christianity -- History of doctrines; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books